High‐level rather than low‐level warming destabilizes plant community biomass production. (25th January 2021) - Quan, Quan; Zhang, Fangyue; Jiang, Lin; Chen, Han Y. H.; Wang, Jinsong; Ma, Fangfang; Song, Bing; Niu, Shuli
Abstract: Ecosystem stability is essential to its sustainable functions and services to humanity. Although climate warming is projected to vary from 1 to 5°C by the end of 21st century, how the temporal stability of plant community biomass production responds to different warming scenarios remains unclear. To fill this knowledge gap, we conducted a 6‐year field experiment with three levels of warming treatments (control, +1.5°C, +2.5°C) by using infrared radiators, in an alpine meadow on the Qinghai–Tibet Plateau. We found that low‐level warming (+1.5°C), compared to the control, did not significantly change the temporal stability of plant community biomass production and its underlying causes, including species diversity, compensatory dynamics, mean–variance scaling, biomass temporal stability of plant population (the average of temporal stability of species biomass production of all species in the community) or dominant species. However, high‐level warming (+2.5°C) significantly reduced them. Species diversity was not a significant predictor of temporal stability of plant community biomass production in this species‐rich ecosystem, regardless of the magnitude of warming, while co‐existing species compensatory dynamics and the biomass temporal stability of dominant species determined the response of temporal stability of plant community biomass production to warming. Synthesis . Our results suggest that the responses of plant community biomass temporal stability and its underlying mechanisms to climate warming depend on warming magnitudes. The findings highlight the various responses of ecosystem functions and services to different warming scenarios and imply that ecosystem will fail to maintain and provide stable biomass‐related services for humanity under high‐level climate warming. Abstract : This study provides empirical evidence that the responses of plant community biomass temporal stability and its causes to climate warming depend on warming magnitudes. We found high‐level rather than low‐level warming destabilized plant community biomass production in an alpine meadow. The finding has important implications for understanding how ecosystem responds to ongoing climate warming, particularly the stability of ecosystem functions and services (e.g. livestock products, bioenergy) below and beyond the 2°C warming target.